An evaluation of the effectiveness of ‘street turn’ as a green logistics tool for the management of empty containers for road haulage in Malaysia / Nur Farizan Tarudin - Tarudin, Nur Farizan (2013)
The problem of empty containers is not unique to Malaysia but also a major problem that is faced by other countries around the world. An effective strategy of managing empty containers not only enable financial savings, but it also has the added advantage of contributing to the well being of the environment. Therefore, several strategies have been identified and implemented to reduce or minimize the environmental impact of moving around empty containers. The practice of industry in Europe in managing the container movement is based largely on two strategies called ‘Depot Direct’ and ‘Street Turn’. These strategies are looked upon as suitable tools for managing container’s entire - journey when there is a haulage by prime movers. However in Malaysia, logistics practitioners have still largely not implemented a similar strategy in the latter that forms the foundation of green logistics thus helping to reduce carbon emissions in Malaysia. Normally, road haulage companies in Malaysia use the ‘Depot Direct’ strategy and from the general observation this strategy is not an environmental friendly process as it entails unnecessary carbon emissions. This author seeks to determine whether there is a cost saving and environmental benefits if there is implementation of a new strategy like ‘Street Turn’ in Malaysia for container haulage operations. The effectiveness of ‘Street Turn’ strategy will be measured systematically looking at the cost of operation gathering after implementation and simple estimation of percentage carbon emission reduction